Regulation of Proapoptotic Mammalian ste20–Like Kinase MST2 by the IGF1-Akt Pathway - Kim, Donghwa (Public Library of Science, 2010)
BACKGROUND: Hippo, a Drosophila serine/threonine kinase, promotes apoptosis and restricts cell growth and proliferation. Its mammalian homolog MST2 has been shown to play similar role and be regulated by Raf-1 via a kinase-independent mechanism and by RASSF family proteins through forming complex with MST2. However, regulation of MST2 by cell survival signal remains largely unknown. METHODOLOGY/PRINCIPAL FINDINGS: Using immunoblotting, in vitro kinase and in vivo labeling assays, we show that IGF1 inhibits MST2 cleavage and activation induced by DNA damage through the phosphatidylinosotol 3-kinase (PI3K)/Akt pathway. Akt phosphorylates a highly conserved threonine-117 residue of MST2 in vitro and in vivo, which leads to inhibition of MST2 cleavage, nuclear translocation, autophosphorylation-Thr180 and kinase activity. As a result, MST2 proapoptotic and growth arrest function was significantly reduced. Further, inverse correlation between pMST2-T117/pAkt and pMST2-T180 was observed in human breast tumors. CONCLUSIONS/SIGNIFICANCE: Our findings demonstrate for the first time that extracellular cell survival signal IGF1 regulates MST2 and that Akt is a key upstream regulator of MST2.